Phosphate fertilization for lettuce in oxisol with high available phosphorus content - Cecílio Filho, Arthur Bernardes [UNESP]; Bonela, Giovani Donizete; Da Cruz, Mara Cristina Pessoa [UNESP]; Rugeles-Reyes, Sergio Manuel [UNESP]; Menezello, Ana Carolina Foresti [UNESP] (UNESP - Universidade Estadual Paulista, 2018)
The intensive cultivation of lettuce in the same area may cause an increase in phosphorus in the soil, causing damage to the environment and plants. The objective of this study was to evaluate the response of three cultivars of lettuce, 'Amanda' (crisp and loose leaves group), 'Karla' (smooth and loose leaves group) and 'Lucy Brown' (crisphead group) and five doses of phosphorus (0, 50, 100, 200 and 300 kg ha-1 of P2O5) in an Oxisol with high levels of this nutrient (136 mg dm-3) in a randomized block design in 3 x 5 factorial experiment with four replications. Statistical analysis was significant for interaction of factors on the P foliar content. Higher values of fresh and dry weight were observed for 'Lucy Brown'; furthermore, all the cultivars had a linear increase with P enhancement, as noticed for P content. The number of leaves (NH) and leaf area (AF) were not influenced by the interaction and set up the quadratic equation where a dose of 161 and 203 kg ha-1 P2O5 provided higher NH and AF, respectively. Phosphorus fertilization promoted significant increases for all lettuce characteristics up to the dose of 300 kg ha-1 P2O5.
Fertilización fosfatada para lechuga en un Oxisol con altos contenidos de fósforo disponible
Keywords: Cultivars; Lactuca sativa; Mineral nutrition